2020
DOI: 10.1177/2278533719887456
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationships Among Work–Life Constructs: A Review

Abstract: Although there has been much research conducted on the work–life interface, the absence of an integrated review of its conceptualization is mystifying to many researchers. This study addresses this gap in the work–family research. The purpose of this article is to review and synthesize existing literature on the work–life interface. The article examines the conceptualization of the key constructs of work life interface, such as work–family conflict (WFC), work–family enrichment (WFE), and work–life balance (WL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
(90 reference statements)
0
12
0
Order By: Relevance
“…The original scale also includes a subscale related to an additional dimension (i.e., behavior-based conflicts), but it was not included for the purpose of the study. The scale was recently identified as one of the most commonly used measures to assess work-family conflict ( Bansal and Agarwal, 2020 ). Carlson et al (2000) have shown the reliability of each subscale, as well as their construct validity (e.g., time-based WLC related positively to the level of work involvement, strain-based WLC related negatively to family and life satisfaction).…”
Section: Methodsmentioning
confidence: 99%
“…The original scale also includes a subscale related to an additional dimension (i.e., behavior-based conflicts), but it was not included for the purpose of the study. The scale was recently identified as one of the most commonly used measures to assess work-family conflict ( Bansal and Agarwal, 2020 ). Carlson et al (2000) have shown the reliability of each subscale, as well as their construct validity (e.g., time-based WLC related positively to the level of work involvement, strain-based WLC related negatively to family and life satisfaction).…”
Section: Methodsmentioning
confidence: 99%
“…Throughout this review, the term "work-life interface" will be used to refer to the relationship between work and non-work domains. This umbrella term includes three different facets [5]: a) negative facet (i.e., conflict), b) positive facet (i.e., enrichment), c) and integrative facet (i.e., balance).…”
Section: Introductionmentioning
confidence: 99%
“…The literature review by Gatrell et al (2012) and Agarwal and Lenka (2015) focused on the specific direction of parenthood and WLB, and WLB of women entrepreneurs, respectively, while structured literature review of Munn and Chaudhuri (2016) was directed toward WLB of dual-earner couples in India and the United States. Further, a meta-analysis review of meaning and measurement of WLB was carried out by Casper et al (2018), a review of conceptualization of work-life constructs by Bansal and Agarwal (2020), and a SLR on WLB in Asia by Le et al (2020). A literature review on WLBPs perspective was presented by Chaudhuri et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Further, a meta-analysis review of meaning and measurement of WLB was carried out by Casper et al. (2018), a review of conceptualization of work–life constructs by Bansal and Agarwal (2020), and a SLR on WLB in Asia by Le et al. (2020).…”
Section: Introductionmentioning
confidence: 99%